Traducciones/perversiones - Panero, Leopoldo María, 1948- (Colección Visor de poesía ;, 2011)
Spanish translator Leopoldo Maria Panero presents bilingual versions of poems by authors such as Catullus to Mick Jagger and Keith Richards, William, Duke of Aquitaine to Robert Browning and Edward Lear.